The Relationship Of Early Mobilization With Operational Wound Healing In Postpartum Mothers With Post Section Ceasarea - Dian Anggri Yanti; Pitriani .; Anita Sri Gandaria Purba; Arfah May Syara; Azizah Safrida Putri (JURNAL KEBIDANAN KESTRA (JKK), 2022)
Early mobilization is a movement that is carried out immediately after surgery. This is done with the aim of restoring the abdominal muscles so they are not stiff and relieve pain so that it can accelerate the wound healing process. Based on Riskesdas North Sumatra 2018, the proportion of delivery methods by cesarean section in North Sumatra Province was 23.89 percent and normal deliveries were 75.95 percent. The purpose of this study was to determine the relationship between early mobilization and surgical wound healing in postpartum mothers post sectio caesarea at the Ibu Kartini Kisaran General Hospital in 2022. This study is a quantitative type of research, with a cross sectional research design using the chi-square test. The population in this study were all postpartum mothers who had undergone post sectio caesarea while at the Ibu Kartini General Hospital in the range of 2022. The sample obtained was 40 people with accidental sampling technique. The statistical test used was the chi square test (p < 0.05). The results of this study indicate that there is a relationship between early mobilization and healing of surgical wounds in postpartum mothers after sectio caesarea at the Kartini General Hospital Kisaran in 2022 with a p value of 0.01. So it is hoped that nurses and midwives will be able to provide education and supervision of the implementation of mobilization for postpartum mothers post sectio caesarea to accelerate wound healing.